Latin America's Future Public Policy Challenges: A Ten‐year Time Horizon. (25th November 2018) - Ward, Peter M.; Wilson, Robert H.
Abstract : This article identifies the most likely public policy challenges and agenda items that policymakers will confront in Latin America 10 years from now. While many of today's challenges will continue to be salient within the public‐policy agenda—the "known knowns"—our goal is to drill down and highlight the most likely sub‐issues and specific policy imperatives and challenges in the medium term (the "known unknowns"). Fifty intensive key informant interviews were conducted with senior and experienced individuals from a range of professional settings, including scholars and academics, agency directors, top think‐tank analysts, heads of non‐governmental organizations, public intellectuals, and senior board members. The article reports on unstructured, one‐on‐one "listening sessions" in which respondents have offered their views on the specific but thus far largely latent public policy issues that they anticipate will need to be addressed looking beyond the status quo ante.